A study of Zarai society through Latin inscriptions (Reading in the surnames and nicknames) - Mohamed El Sagheer, Karim (The Algerian Historical Journal, 2026)
The archaeological writings (Epigraphy) are among the evidence that played an important role in writing ancient history. Epigraphic texts have contributed to completing the picture of human life. By analysing these writings, the mechanisms that move societies, as well as the various social, political and cultural systems in ancient times can be understood. This study aims to identify the components of Zarai society through restricted Latin writings at the region’s level. Thus, it was based on the origins of the surnames and nicknames of the region’s inhabitants. Moreover, this study shed light on the militray side represented by the most important teams and soldiers that camped in the city of Zari. Finaly, the study concluded the most important Gods and beliefs prevailed in this society